2015
DOI: 10.1111/pde.12560
|View full text |Cite
|
Sign up to set email alerts
|

Isothiazolinones: Sensitizers Not to Miss in Children

Abstract: Isothiazolinone is known to be a sensitizer and a frequent cause of contact dermatitis in adults. Cases of contact dermatitis have also recently been reported in children. Derivatives of isothiazolinone, such as methylisothiazolinone (MI) and methylchloroisothiazolinone (MCI), are commonly used in the care products of babies and children. This allergen should not be missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Notwithstanding, the incidence of allergic contact dermatitis has increased because the concentration of MI required to achieve adequate biocidal activity is greater than the combination of MCI/MI. 7 Research finds that the individuals most at risk are women older than 40 years with facial eczema who use cosmetics. 3 Moreover, in those sensitized, most products used were either leave-on products or wet wipes as opposed to rinse-off products like shampoos.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the incidence of allergic contact dermatitis has increased because the concentration of MI required to achieve adequate biocidal activity is greater than the combination of MCI/MI. 7 Research finds that the individuals most at risk are women older than 40 years with facial eczema who use cosmetics. 3 Moreover, in those sensitized, most products used were either leave-on products or wet wipes as opposed to rinse-off products like shampoos.…”
Section: Discussionmentioning
confidence: 99%
“…test) , Chang and Nakrani reported six children (four girls, two boys, ages 3–8 years) with ACD to MI‐containing wet wipes using an epicutaneous patch test, and Admani et al published a case report of perianal dermatitis in a 9‐year‐old boy caused by contact allergy to MI‐containing wet wipes using an epicutaneous patch test. Quenen et al , in Geneva, Switzerland, recently reported four pediatric cases of MI contact allergy and stated that “it remains underdiagnosed in the United States because it is still tested in combination with MCI”. Thus the true prevalence of MCI/MI and specifically MI sensitization in children is unknown.…”
Section: Published Pediatric Patch Test Results To Methylchloroisothimentioning
confidence: 99%
“…Not testing MI alone has been reported to potentially miss 33% to 60% of patients sensitive to MI . Furthermore, Quenan et al noted that “[p]ractitioners widely use the [epicutaneous patch test] but it contains only the combination MCI/MI. This should raise awareness of the fact that MI should also be tested as a separate entity”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The most common sources of exposure are wet wipes, cosmetics, and cleansing products. 6 Slime is a non-Newtonian liquid that has gained popularity among children because of its easily malleable structure. In addition to commercially available forms, there are numerous written or visual online recipes for the preparation of homemade slime.…”
Section: Discussionmentioning
confidence: 99%